1989
DOI: 10.1002/1097-0142(19890115)63:2<364::aid-cncr2820630228>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Peritioneal carcinomatosis in nongynecologic malignancy. A prospective study of prognostic factors

Abstract: Regional recurrence of malignant tumors in the peritoneal cavity usually signifies a poor prognosis for the host and often results in gastrointestinal complications requiring surgical intervention. One hundred patients with nongynecological malignancies found with peritoneal carcinomatosis were followed prospectively. The most common primary tumors were colorectal (N = 45) and pancreatic (N = 20) carcinoma. When associated with pancreatic carcinoma, 65% of patients had liver metastases and 60% had ascites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
283
1
15

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(306 citation statements)
references
References 13 publications
7
283
1
15
Order By: Relevance
“…Peritoneal carcinomatosis, once established, is associated with poor prognosis and a median survival of 1-6 months [3,17,18]. Our study also showed that the prognosis is poor with a median survival of 9.4 months after peritoneal recurrence, which was worse than that after distant metastasis without peritoneal recurrence (14.6 months).…”
Section: Discussionsupporting
confidence: 51%
“…Peritoneal carcinomatosis, once established, is associated with poor prognosis and a median survival of 1-6 months [3,17,18]. Our study also showed that the prognosis is poor with a median survival of 9.4 months after peritoneal recurrence, which was worse than that after distant metastasis without peritoneal recurrence (14.6 months).…”
Section: Discussionsupporting
confidence: 51%
“…Accordingly, almost 60% of all causes of death from gastric cancer is from PC. However, the prognosis of the patients with established PC or peritoneal recurrence is very poor [5,6] and no standard treatment for PC has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of factors prognostic for survival showed that differentiation of the primary tumor did not affect the prognosis of patients with PC. Mean and median OS times in these patients with PC from non-gynecologic malignancies were 6.0 and 3.1 months, respectively (6,35).…”
Section: Discussionmentioning
confidence: 98%
“…The prognosis is poor for patients with macroscopic PC, which is responsible for ~60% of all gastric cancer-associated mortalities (33,34). Two prospective studies assessed outcomes in patients with PC from non-gynecologic malignancies: Gastric, colorectal and pancreatic cancer (6,35). The presence of ascites was associated with poor survival of patients with gastric or pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%